IN VITRO BROMODEOXYURIDINE LABELING INDEX : PROGNOSTIC ROLE IN EARLY STAGE BREAST CANCER - Ersin Selçuk Ünal; Beyza Özçınar; Vahit Özmen; Ayhan Bilir; Abdullah İğci; Mahmut Müslümanoğlu; Mustafa Keçer; Mesut Parlak (European Journal of Breast Health, 2006)

(untitled)
AIM: Various putative prognostic factors were studied in early breast cancer to evaluate local and systemic recurrence rates and make a decision for adjuvant treatments. In this study, the prognostic value of bromodeoxyuridine labeling index (BrdU LI) has been investigated in patients with early breast cancer and compared with other established clinical and biological factors.PATIENTS AND METHODS: After a staging work-up, the BrdU LI has been prospectively analysed in primary tumor fragments obtained from 81 consecutive patients with early breast cancer.RESULTS: The mean and median BrdU LI values for the whole group of patients were 6.22% and 5.18% (range: 0-27.33), respectively. Further analysis revealed that the BrdU LI rate was significantly higher in patients who had local recurrence (p= 0.026), or systemic metastases (p= 0.004).CONCLUSION: Our results suggest that the BrdU LI might be used as a prognostic marker to identify of patients at higher risk of relapse and to select the most appropriate adjuvant treatment for an individual patient.